The draft genome sequence of a desert tree Populus pruinosa - Yang, Wenlu (Gigascience, 2017)
Populus pruinosa is a large tree that grows in deserts and shows distinct differences in both morphology and adaptation compared to its sister species, P. euphratica. Here we present a draft genome sequence for P. pruinosa and examine genomic variations between the 2 species. A total of 60 Gb of clean reads from whole-genome sequencing of a P. pruinosa individual were generated using the Illumina HiSeq2000 platform. The assembled genome is 479.3 Mb in length, with an N50 contig size of 14.0 kb and a scaffold size of 698.5 kb; 45.47% of the genome is composed of repetitive elements. We predicted 35 131 protein-coding genes, of which 88.06% were functionally annotated. Gene family clustering revealed 224 unique and 640 expanded gene families in the P. pruinosa genome. Further evolutionary analysis identified numerous genes with elevated values for pairwise genetic differentiation between P. pruinosa and P. euphratica. We provide the genome sequence and gene annotation for P. pruinosa. A large number of genetic variations were recovered by comparison of the genomes between P. pruinosa and P. euphratica. These variations will provide a valuable resource for studying the genetic bases for the phenotypic and adaptive divergence of the 2 sister species.